A new sequence motif linking lissencephaly, Treacher Collins and oral-facial-digital type 1 syndromes, microtubule dynamics and cell migration. - Emes, R; Ponting, C (2001)
A previously unidentified sequence motif has been identified in the products of genes mutated in Miller-Dieker lissencephaly, Treacher Collins, oral-facial-digital type 1 and contiguous syndrome ocular albinism with late onset sensorineural deafness syndromes. An additional homologous motif was detected in a gene product fused to the fibroblast growth factor receptor type 1 in patients with an atypical stem cell myeloproliferative disorder. In total, over 100 eukaryotic intracellular proteins are shown to possess a LIS1 homology (LisH) motif, including several katanin p60 subunits, muskelin, tonneau, LEUNIG, Nopp140, aimless and numerous WD repeat-containing beta-propeller proteins. It is suggested that LisH motifs contribute to the regulation of microtubule dynamics, either by mediating dimerization, or else by binding cytoplasmic dynein heavy chain or microtubules directly. The predicted secondary structure of LisH motifs, and their occurrence in homologues of Gbeta beta-propeller subunits, suggests that they are analogues of Ggamma subunits, and might associate with the periphery of beta-propeller domains. The finding of LisH motifs in both treacle and Nopp140 reinforces previous observations of functional similarities between these nucleolar proteins. Uncharacterized LisH motif-containing proteins represent candidates for other diseases associated with aberrant microtubule dynamics and defects of cell migration, nucleokinesis or chromosome segregation.